(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Rayleigh-Taylor instability (RTI) is frequently observed in nature like oil extraction process, -sequestration and in the laboratory like chromatographic separation techniques. Suppression and control of RTI to get desired result is very important aspect. Mathematical modelling as well as various numerical methods to get results are available in literature. But in this work, we studied the problem using COMSOL and consistent results are obtained. Our finding shown that less instability is obtained in mapped mesh as compared to triangular meshing. Also, our finds suggest that forward finger and backward finger length are almost same.